THE SYNERGY OF FORENSIC MEDICINE AND BLOODSTAIN PATTERN ANALYSIS IN DETERMINING THE MANNER OF DEATH - Stojanović, Ivan; Miljković, Milica; Nikolić, Marija; Pinterović, Bogdan; Veličković, Saša; Pančić, Dimitrije (Acta medicae Medianae, 2026)
A forensic pathologist and a bloodstain pattern analyst are involved in determining the manner and the mechanism of death, but based on different scientific approaches. Our work presents the benefits of a holistic approach to forensic expertise. We have analyzed and described three cases. In all cases, the initial police investigation had concluded the wrong manner of violent death (accident, suicide, homicide), but the subsequent synergy of forensic autopsy and bloodstain pattern analysis (BPA) determined the true nature of death. BPA in Serbia is a relatively new forensic discipline. Police authorities (Crime scene evidence technicians) in Serbia are familiar with BPA, but according to our legislation, they are not allowed to provide expertise in the courtroom. The benefits of synergistic expertise in forensic medicine and BPA are more than evident in our cases. Therefore, the education of specialists in forensic medicine in BPA will be useful for solving suspicious and indistinct cases.
Keywords: forensic medicine, autopsy, bloodstain, bloodstain pattern analysis